Recreational Therapy Competencies, Part 2: Findings from the ATRA Competencies Study. - Hawkins, Brent L.; Kemeny, Betsy; Porter, Heather R. (Therapeutic Recreation Journal, 2020)
The American Therapeutic Recreation Association's (ATRA) Competencies Study was the final phase of a two-part, multi-year study to better understand the competencies of Recreational Therapists (RTs) across treatment settings and service sectors. One thousand, three hundred and seventy seven RTs were assessed on 747 items within seven areas of RT practice identified in ATRA's Delphi Study. Each RT rated the extent that each item is being treated, utilized, or provided in their RT practice, their perceived knowledge and skills in relation to the items, and if they were interested in gaining more knowledge related to each item. Results are reported regarding areas of RT practice that were highly, moderately, and lowly rated to further capture the scope of practice of RT as well as identify areas of strength and opportunity to bolster RT practice. Opportunities within the profession to apply these findings are discussed.